The Role of Specialized Judicial Bodies for Regional Head Elections in Election Law Enforcement - Hindiawati, Wahyu (LEGAL BRIEF, 2024)
The complex problems of electoral justice require the need for comprehensive reconstruction of the justice system. The large number of institutions involved in the process of resolving election cases makes the integration of the electoral justice system very urgent. Moreover, Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning the Determination of Government Regulations in Lieu of Law Number 2014 concerning the Election of Governors, Regents and Mayors into Law has mandated the formation of a special judicial body. From the description of the problem, the problem is formulated as follows: How will the Special Regional Election Judicial Body be designed in Indonesia in the future? Meanwhile, the method used in this research is a normative legal research method, by examining Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning the Determination of Government Regulations in Lieu of Law Number 2014 concerning the Election of Governors, Regents and Mayor Becomes Law. The conclusion of this research is as follows: The future design of the Special Judicial Body for Regional Elections in Indonesia refers to the special judicial body specified in Law Number 10 of 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning Determination of Government Regulations in Lieu of Laws -Law Number 2014 concerning the Election of Governors, Regents and Mayors into Law Article 157 paragraph 1, as well as Article 157 paragraph (1) Law Number 8 of 2015 should be formed and remain under the auspices of the Constitutional Court on a par with other courts. both at the district or city and provincial levels. Apart from that, all regional election disputes, both process disputes and result disputes, are decided by the special Regional Election Judicial Body